How do movements to produce letters become automatic during writing acquisition? Investigating the development of motor anticipation. (March 2015) - Kandel, Sonia; Perret, Cyril
Learning how to write involves the automation of grapho-motor skills. One of the factors that determine automaticity is motor anticipation . This is the ability to write a letter while processing information on how to produce following letters. It is essential for writing fast and smoothly. We investigated how motor anticipation processes build up during the period of handwriting automation. Children aged 8, 9 and 10 years had to write two letters ( ll, le, ln ) in cursive writing on a digitizer. Motor anticipation referred to processing changes in size ( ll vs. le ) and rotation direction ( le vs. ln ) of the second letter while writing the l . We recorded three measures on the l upstroke and downstroke. The movement time data indicate that the l upstroke was very variable. The l 's downstroke duration was shorter for ll than le and the latter was in turn shorter than ln . This pattern was already observed at age 8. Trajectory length data revealed that the anticipation of a single parameter such as size change is enough to produce a trajectory increase but the addition of parameters is not cumulative, as we observed for stroke duration. The dysfluency data indicated that at age 8, dysfluency values were equivalent for upstrokes and downstrokes. At ages 9 and 10, the children produced more dysfluency on downstrokes than upstrokes. Previous studies on writing with adults have shown that the anticipation of the following letter affects the production of the l 's downstroke. The production of the upstroke did not vary. This experiment suggests that learning to anticipate in handwriting production requires: a) rendering the movements to produce the upstroke constant; and b) modulating the downstroke as a function of the spatial characteristics of the following letter. The pattern of movement time data suggest that motor anticipation would start to be adult-like at around age 9. Dysfluency and latency measures do not seem to be very informative about the development of motor anticipation in handwriting.